2004
DOI: 10.1103/physrevd.70.024009
|View full text |Cite
|
Sign up to set email alerts
|

Dirty black holes: Symmetries at stationary nonstatic horizons

Abstract: We establish that the Einstein tensor takes on a highly symmetric form near the Killing horizon of any stationary but nonstatic ͑and nonextremal͒ black hole spacetime. ͓This follows up on a recent article by the current authors ͑gr-qc/0402069͒, which considered static black holes.͔ Specifically, at any such Killing horizon-irrespective of the horizon geometry-the Einstein tensor block-diagonalizes into ''transverse'' and ''parallel'' blocks, and its transverse components are proportional to the transverse metr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
223
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(232 citation statements)
references
References 28 publications
6
223
2
1
Order By: Relevance
“…However, this simple relation concerning the mode spacing does not seem to hold when m ≤ 0. Analytic derivations for the spacing in the QNM imaginary parts have been provided in [45] and [46]. These calculations use the fact that QNM's are poles in the scattering amplitude of the relevant wave equation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this simple relation concerning the mode spacing does not seem to hold when m ≤ 0. Analytic derivations for the spacing in the QNM imaginary parts have been provided in [45] and [46]. These calculations use the fact that QNM's are poles in the scattering amplitude of the relevant wave equation.…”
Section: Discussionmentioning
confidence: 99%
“…These observers have the four velocity u α = ξ α / −ξ β ξ β . After some straightforward tensor manipulations (for similar calculations, see [16] ), we find that the on-horizon (η = 0) components of the Einstein tensor, as seen by the stationary observers, are…”
Section: Kerr-newman Spacetimementioning
confidence: 99%
“…If the thermodynamic interpretation of gravity is to be generic, one needs to go beyond these assumptions and check whether the results remain valid for more general spacetimes. Intuitively we expect these results to hold more generally because one of the crucial inputs (arising from spherical symmetry) is the equality of T t t and T r r on the horizon and it has been shown that this result is valid even for general stationary killing horizons [16]. So a step forward would be to study the near horizon structure of the field equations for a more general spacetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Even before imposing any field equations, it can be shown that the requirement of finite curvature at the horizon sharply restricts the behavior of the metric: it must have a near-horizon expansion [66] …”
Section: A Generic (3 + 1)-dimensional Black Holementioning
confidence: 99%